New therapeutic applications of ozenoxacin in superficial skin infections - Gema García Ron; María Villa Arranz (PAGEPress Publications, 2021)
In recent years, the incidence of community-acquired methicillin-resistant S. aureus skin infections (CA-MARSA) has increased in pediatric population without associated risk factors. Ozenoxacin 10mg/g is a topical quinolone that has shown high activity on strains of S. aureus, S. pyogenes and other Gram-positive bacteria sensitive and resistant to methicillin, other quinolones, mupirocin and fusidic acid. Ozenoxacin 10mg/g cream was applied twice a day for 5 days in pediatric patients with superficial skin infections other than non-bullous impetigo where oral antibiotics were not needed. Therapeutic success was achieved in 93.7% of the patients after 5 days of treatment, with a 98.2% decrease in the mean SIRS scale of symptoms. No adverse reaction was reported during treatment. Given the achieved effectiveness, safety, and adherence of the treatment, we believe that pediatricians should consider this topical antibiotic for the treatment of other superficial skin infections, without limiting its use to non-bullous impetigo.